2022
DOI: 10.1155/2022/5500077
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CALL on Vocabulary Learning, Speaking Skill, and Foreign Language Speaking Anxiety: The Case Study of Indonesian EFL Learners

Abstract: Using computer-assisted language learning (CALL) in English language learning has not received the attention it deserves in Indonesian EFL context; thus, this study tried to inspect the impacts of CALL on Indonesian EFL learners’ vocabulary learning, speaking skill, and speaking anxiety. To reach this end, the Oxford Quick Placement Test (OQPT) was administered to 103 Indonesian EFL students, and 60 of them whose English proficiency levels were intermediate were chosen as the respondents of this investigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…The enormous development of new information technologies and communication has made drastic changes in the educational systems over recent decades (Bashori et al, 2020;Rahimi et al, 2021). Applying CALL has increased vastly and impacted substantially educational improvements (Hanafiah et al, 2022). CALL is one of the promising methods that have a strong effect on boosting EFL learners' competence (Tafazoli et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The enormous development of new information technologies and communication has made drastic changes in the educational systems over recent decades (Bashori et al, 2020;Rahimi et al, 2021). Applying CALL has increased vastly and impacted substantially educational improvements (Hanafiah et al, 2022). CALL is one of the promising methods that have a strong effect on boosting EFL learners' competence (Tafazoli et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…They found that the experimental groups significantly outflanked the control group at the end of the interventions. Finally, Hanafiah et al (2022) inspected the effects of CALL on Indonesian EFL learners' vocabulary learning, speaking skill, and speaking anxiety. Their results indicated that CALL positively affected the participants' vocabulary learning, speaking skill, and speaking anxiety.…”
Section: Effects Of Computer-assisted Language Learning and Mobile-as...mentioning
confidence: 99%
“…Several studies revealed a positive relationship between examination results and various evaluation modalities [75% (Olga and Victor, 2021);58.65% (AlTameemy et al, 2020); 30.5% (Hidalgo-Camacho et al, 2021); no percentage (Chen et al, 2021;Hanafiah et al, 2022)]. This assertion was supported by the reviews of (Rofiah and Waluyo, 2020;Nguyen, 2021).…”
Section: Students' Perceptions Of E-assessmentmentioning
confidence: 88%
“…Male students have a more favorable approach to e-assessment than female students due to differences in technological implementation ability (AlTameemy et al, 2020), and more proficient learners were more inclined to accept online testing (Rofiah and Waluyo, 2020). Nevertheless, students expressed definite concern about online learning that would hinder their progress and test results (Olga and Victor, 2021;Hanafiah et al, 2022;Poonpon et al, 2021). As Hidalgo-Camacho et al (2021) cautioned, the lack of equipment, unstable internet connection, or other possible technical challenges can negatively affect their emotional state.…”
Section: Students' Perceptions Of E-assessmentmentioning
confidence: 99%
“…Even though using the foreign language orally is a requirement for students, they always complain about not being able to speak fluently as most of them are unwilling to speak even in language classes. Many studies have tried to uncover the factors that may facilitate oral communication in a foreign language and reduce speaking anxiety (Hanafiah, et al 2022;Sadighi & Dastpak, 2017;Chou, 2018;Pribyl, Keaten, and Sakamoto, 2001;Tsi-plakides and Keramida, 2009). This research aims at reducing speaking anxiety and encouraging willingness to communicate in ESL speaking classes with the help of mindfulness training.…”
Section: Introductionmentioning
confidence: 99%